Learning from the past? An exploratory study of familial food socialization processes using the lens of emotional reflexivity. (12th November 2018) - Kharuhayothin, Tanyatip; Kerrane, Ben
Abstract : Purpose: This paper aims to explore the parental role in children's food socialization. More specifically, it explores how the legacy of the past (i.e. experiences from the participant's own childhood) works to inform how parents, in turn, socialize their own children within the context of food, drawing on theories of consumer socialization, intergenerational influence and emotional reflexivity. Design/methodology/approach: To seek further understanding of how temporal elements of intergenerational influence persist (through the lens of emotional reflexivity), the authors collected qualitative and interpretative data from 30 parents from the UK using a combination of existential–phenomenological interviews, photo-elicitation techniques and accompanied grocery shopping trips (observational interviews). Findings: Through intergenerational reflexivity, parents are found to make a conscious effort to either "sustain" or "disregard" particular food practices learnt from the previous generation with their children (abandoning or mimicking the behaviours of their own parents within the context of food socialization). Factors contributing to the disregarding of food behaviours (new influencer, self-learning and resistance to parental power) emerge. A continuum of parents is identified, ranging from the "traditionalist" to "improver" and the "revisionist". Originality/value: By adopting a unique approach in exploring the dynamic of intergenerational influence through the lens of emotional reflexivity, this study highlights the importance of the parental role in socializing children about food, and how intergenerational reflexivity helps inform parental food socialization practices. The intergenerational reflexivity of parents is, thus, deemed to be crucial in the socialization process.